Strategi Komunikasi Dinas Kesehatan Kota Serang Mengenai Program Gerakan Masyarakat Hidup Sehat (GERMAS) - Rahmi Winangsih; Hairun Nisa (Magister Komunikasi Universitas Sultan Ageng Tirtayasa, 2020)
Dissemination of information about the Healthy Living Community Movement needs to be done thoroughly, bearing in mind that the number of people with non-communicable diseases has increased significantly from year to year. The right communication strategy needs to be done by Serang City Health Office. Therefore through the Sign Flow Model